Mobile Application Development Approaches: A Comparative Analysis on the Use of Storage Space - Fernández Sosa, Juan (2018)
The purpose of software development is meeting both functional and non-functional requirements. In mobile device applications, non-functional requirements are more relevant due to the restrictions inherent to these devices. One of these restrictions is the availability of limited storage space. Therefore, the size of a mobile application affects user preference for use. In this article, we assess how the choice of a mobile application development approach affects the final size of the application; we focus our analysis on text-, audio- and video-based applications